2021
DOI: 10.1590/1414-431x2020e10865
|View full text |Cite
|
Sign up to set email alerts
|

Effects of respiratory muscle training on parasympathetic activity in diabetes mellitus

Abstract: This study verified the effects of respiratory muscle training (RMT) on hemodynamics, heart rate (HR) variability, and muscle morphology in rats with streptozotocin-induced diabetes mellitus (DM). Thirty-six male Wistar rats were randomized into 4 groups and 34 completed the study: i) sham-sedentary (Sham-ST; n=9); ii) sham-RMT (Sham-RMT; n=9); iii) DM-sedentary (DM-ST; n=8); and iv) DM-RMT (DM-RMT; n=8). Hemodynamics were assessed by central cannulation, and R-R intervals were measured by electrocardiogram. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Patients with T2DM and autonomic dysfunction have impaired nerve blood supply, in other words, nerve conduction affected with consequent neuropathy, being more impaired than those without nerve injury [ 31 , 32 ] . Regarding autonomic modulation, one study by our group showed that IMT improved autonomic function in diabetic patients [ 33 ] with increased parasympathetic activity. In healthy individuals, the use of IMT with a load of 30% MIP provides an increase in vagal modulation, while higher loads can determine a predominance of sympathetic modulation [ 34 , 35 ] .…”
Section: Discussionmentioning
confidence: 99%
“…Patients with T2DM and autonomic dysfunction have impaired nerve blood supply, in other words, nerve conduction affected with consequent neuropathy, being more impaired than those without nerve injury [ 31 , 32 ] . Regarding autonomic modulation, one study by our group showed that IMT improved autonomic function in diabetic patients [ 33 ] with increased parasympathetic activity. In healthy individuals, the use of IMT with a load of 30% MIP provides an increase in vagal modulation, while higher loads can determine a predominance of sympathetic modulation [ 34 , 35 ] .…”
Section: Discussionmentioning
confidence: 99%